2022
DOI: 10.3389/fpubh.2022.1029740
|View full text |Cite
|
Sign up to set email alerts
|

Second-dose measles vaccination and associated factors among under-five children in urban areas of North Shoa Zone, Central Ethiopia, 2022

Abstract: IntroductionMeasles remain a leading cause of vaccine-preventable infant mortality. In Africa, about 13 million cases and 6,50,000 deaths occur annually, with Sub-Saharan Africa having the highest morbidity and mortality. Ethiopia launched second-dose measles vaccination into the routine immunization program in the second year of life in 2019. However, little has been known about the coverage of the second-dose measles vaccine. Therefore, the purpose of this study was to assess the level of second-dose measles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
5
11
1
Order By: Relevance
“…However, the result of the study is higher than the studies conducted in Indonesia (54%) ( 31 ), Kenya (56.2%) ( 32 ), North Shewa, Ethiopia (42.5%) ( 17 ), and Jabitehnan district, Ethiopia (48.1%) ( 23 ). For the study conducted in Kenya, the possible reason may be due to the difference in the study population (they included children aged 24–59 months, whereas, for this study, the ages included were 24–36 months).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…However, the result of the study is higher than the studies conducted in Indonesia (54%) ( 31 ), Kenya (56.2%) ( 32 ), North Shewa, Ethiopia (42.5%) ( 17 ), and Jabitehnan district, Ethiopia (48.1%) ( 23 ). For the study conducted in Kenya, the possible reason may be due to the difference in the study population (they included children aged 24–59 months, whereas, for this study, the ages included were 24–36 months).…”
Section: Discussioncontrasting
confidence: 66%
“…The proportion of children aged 24–36 months who had received MCV2 in addition to MCV1, regardless of when they received the MCV1, were considered to have received MCV2 and were coded as “1”; otherwise, as “0” ( 15 , 17 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tadesse and colleagues explored associated factors related to second-dose measles vaccination among under-five children in urban areas of North Shewa Zone, Oromia, Ethiopia, using a community-based cross-sectional study [24]. The study found a low (42.5%) level of second-dose measles vaccination (MCV2) among children in urban areas of the study area.…”
Section: Immunization Challenges and Predictors In Urban And Peri-urbanmentioning
confidence: 99%
“…The study from Oromia (Tadesse et al) also recommended some strategies for increasing the uptake of MCV2, including shortening the waiting time for vaccination at the health facility to within half an hour, intensifying awareness for parents and caregivers, and paying particular attention to mothers who are older than 36 years of age [24].…”
Section: Identified Pro-equity Strategiesmentioning
confidence: 99%